The Relation Of Earthquake And Migration: January 24, 2020 Elazig Earthquake Example - Peker, Ayşe Esra; Şanlı, İrem (Fırat University, 2022)
By different times and for different purposes throughout history, Turkey has hosted much immigration. This is the most important cause of homeownership, as is Turkey's geographical location is on a major migration route. This process is accompanied by various international problems of Turkey with the addition of a more comprehensive immigration policy in this regard has emerged as a necessity of creation. The common occurrence within the phenomenon of migration, which has tragic and extremely complex consequences for humanity, is forced migration. The forced migration group includes wars, internal conflicts, political pressures, and poverty, as well as natural disasters such as famine, drought, flood, and earthquake. In this study, it is aimed to deal with the perception of migration that may arise after natural disasters. In the study, a survey was conducted for the process after the 2020 Elazığ earthquake, and it was aimed to develop policy recommendations by determining the socioeconomic effects of the earthquake, as well as determining the direction of the migration perception that may arise and ensuring effective management of the process. The study is aimed to contribute to the literature in terms of developing the migration policies of Turkey. Therefore Turkey, a seismic zone country, can be prepared for the mobility of population due to an earthquake, which she may encounter in the next years.

Tarih boyunca farklı zamanlar ve farklı amaçlar doğrultusunda Türkiye birçok göçe ev sahipliği yapmıştır. Bu ev sahipliliğinin en önemli nedeni coğrafi konum itibariyle Türkiye’nin önemli göç rotaları üzerinde olmasıdır. Göç sorunsalı 20. yüzyılın ikinci yarısından itibaren şekil değiştirerek küreselleşme kavramı ile yeni bir boyut kazanmıştır. Bu sürece eşlik eden çeşitli uluslararası sorunlarında eklenmesiyle Türkiye’nin bu konuda daha kapsamlı göç politikası oluşturma zorunluluğu ortaya çıkmıştır. İnsanlık açısından trajik ve son derece karmaşık sonuçlar doğuran göç olgusu içerisinde yaygın olarak gerçekleşeni, zorunlu göçlerdir. Zorunlu göç grubu içerisinde savaşlar, iç çatışmalar, siyasal baskılar ve yoksulluğun yanı sıra kıtlık, kuraklık, sel ve deprem gibi doğal afetler yer almaktadır. Bu noktadan yola çıkan çalışmada doğal afetler sonrası ortaya çıkabilecek göç algısı ele alınmak istenmiştir. Çalışmada 2020 Elazığ depremi sonrası yaşanan sürece yönelik anket çalışması yapılmış, depremin sosyoekonomik etkileri ortaya konmasının yanı sıra ortaya çıkabilecek göç algısının yönü belirlenerek sürecin etkin yönetiminin sağlanabilmesine yönelik tespitlerde bulunularak politika önerileri geliştirilmesi hedeflenmiştir. Çalışmanın yerel nitelik taşıması ve deprem kuşağında yer alan Türkiye’nin önümüzdeki yıllarda deprem sonrası yaşayabileceği nüfus hareketliliğine hazırlıklı olması açısından göç politikalarının geliştirilmesi bağlamında çalışmanın literatüre katkı sağlaması hedeflenmektedir.
DEPREM ve GÖÇ İLİŞKİSİ: 24 OCAK 2020 ELAZIĞ DEPREM ÖRNEĞİ